Determining the Sign of the Z-Penguin Amplitude - Haisch, U; Weiler, A (2007)
We point out that the precision measurements of the pseudo observables R_b^0, A_b, and A_FB^0,b performed at LEP and SLC suggest that in models with minimal-flavor-violation the sign of the Z-penguin amplitude is identical to the one present in the standard model. We determine the allowed range for the non-standard contribution to the Inami-Lim function C and show by analyzing possible scenarios with positive and negative interference of standard model and new physics contributions, that the derived bound holds in each given case. Finally, we derive lower and upper limits for the branching ratios of K^+ -> pi^+ nu nubar, K_L -> pi^0 nu nubar, K_L -> mu^+ mu^-, B -> X_d,s nu nubar, and B_d,s -> mu^+ mu^- within constrained minimal-flavor-violation making use of the wealth of available data collected at the Z-pole.